2019
DOI: 10.1039/c9tc00237e
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the local structure of dopants, doping efficiency, and luminescence properties of lanthanide-doped CsPbCl3 perovskite nanocrystals

Abstract: Our results greatly deepen the understanding of the structural and photophysical properties of lanthanide-doped lead halide perovskite NCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(79 citation statements)
references
References 67 publications
3
73
0
Order By: Relevance
“…In the FT,the relative decrease in the peak position compared with the actual interatomic distance could be attributed to the photoelectron phase shift. [16] In conclusion, all these results support that the doped Tb 3+ ions occupied In 3+ sites.…”
Section: Forschungsartikelsupporting
confidence: 62%
“…In the FT,the relative decrease in the peak position compared with the actual interatomic distance could be attributed to the photoelectron phase shift. [16] In conclusion, all these results support that the doped Tb 3+ ions occupied In 3+ sites.…”
Section: Forschungsartikelsupporting
confidence: 62%
“…A long PL lifetime >2 ms was reported for the Laporte forbidden NIR Yb 3+ emission, suggesting incorporation of the dopants into the host lattice 22 . Local structure studies also confirm that Yb 3+ occupies the octahedral Pb 2+ site of CsPbCl 3 NCs 33 . Gamelin and coworkers reported añ 190% PL QY from not only NCs but also bulk-like thin films of Yb 3+ -doped CsPbCl 3…”
Section: Luminescence Via Spectral Shifting From Lanthanide-doped Cspmentioning
confidence: 70%
“…Recent studies have demonstrated successful B‐site doping using alkaline‐earth metal ions (Mg 2+ , Ba 2+ , Sr 2+ ), [ 14–17 ] transition metal ions (Cu 2+ , Cd 2+ , Ag + , Zn 2+ ), [ 18–21 ] metalloid ions (Sn 2+ , Bi 3+ ), [ 22–24 ] and lanthanide ions (Ce 3+ , Tb 3+ , Yb 3+ ). [ 25–27 ] Despite these advantages, dopants may also lead to negative effects on the properties of NCs. Begum et al.…”
Section: Introductionmentioning
confidence: 99%